Cross-culture Communication for Undergraduate International Students: A case study of one university in Chonburi province - Luo, Haocheng; Leeniwa, Jindapa; Charoenarpornwattana, Paratchanun (Business Administration and Economics Review, 2025)
This objective research aims to explore the cross-culture communication problem for undergraduate international students and to provide recommendations for undergraduate international students. It is a case study of one university in Chonburi province using phenomenological methods. Semi-structured interviews were conducted with 12 undergraduate international students from different cultural backgrounds to understand their experiences and challenges. The results found that the cross-culture communication problem for undergraduate international students can be categorized into 8 problems: 1) communication adaptation, 2) verbal communication, 3) non-verbal communication, 4) language barriers, 5) inclusion barriers, 6) culture barriers, 7) environment barriers, and 8) attitudinal barriers. The recommendations for undergraduate international students can be categorized into 2 topics: 1) culture and 2) language.